2009
DOI: 10.1159/000255971
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Lesions and Lacunar Infarcts Are Independently and Differently Associated with Brain Atrophy: The SMART-MR Study

Abstract: Objective: To investigate the independent association of white matter lesions (WML) and lacunar infarcts (LI) with measures of global brain atrophy on MRI. Methods: Within the SMART-MR study, a cohort study among patients with manifest arterial disease, cross-sectional analyses were performed in 840 patients (mean age 58 ± 10 years, 80% male) without cortical, large subcortical or infratentorial infarcts. Brain segmentation was used to quantify volumes of brain tissue, cerebrospinal fluid and WML. Total brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
47
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 67 publications
4
47
1
Order By: Relevance
“…Previous studies have reported correlations of WML with both subcortical and cortical atrophy. 8,36 Even though WML and brain atrophy are obviously interrelated processes, our results suggest that they independently and differentially contribute to cognitive impairment.…”
Section: Figure 2 Combined Effects Of White Matter Lesions (Wml) and mentioning
confidence: 76%
“…Previous studies have reported correlations of WML with both subcortical and cortical atrophy. 8,36 Even though WML and brain atrophy are obviously interrelated processes, our results suggest that they independently and differentially contribute to cognitive impairment.…”
Section: Figure 2 Combined Effects Of White Matter Lesions (Wml) and mentioning
confidence: 76%
“…Moreover, MR measures of brain atrophy are related to the accrual of subcortical vascular lesions [18,19], thus suggesting that neuroaxonal loss could be the final common pathway of the pathological process underlying CADASIL [20,21]. Finally, the burden of subcortical lesions has been related to cortical apoptosis, confirming that cortical atrophy may follow the axonal damage in the underlying white matter [22].…”
Section: Discussionmentioning
confidence: 99%
“…6 Some studies 2,10 render these classifications artificial. Others claim that they are arbitrary 11 and contrary to pathologic evidence of common vascular mechanisms, or they have suggested that PVWMH and DWMH volumes are highly correlated and have found that their spatial analysis failed to identify distinct subpopulations for PVWMH and DWMH. 12 Thus, a robust analysis of PVWMH morphology, distribution, and clinical correlates is required to determine a more appropriate classification of these hyperintense regions and their associations.…”
mentioning
confidence: 99%